2019
DOI: 10.21815/jde.019.066
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Undergraduate Education Related to Students' Academic Performance in the First Year of Dental School

Abstract: The aim of this study was to improve understanding of predictors of student success in dental school. A total of 178 student records from the Classes of 2015 and 2016 at a U.S. dental school were reviewed for this retrospective study. The records assessed included admissions files with such elements as scores on the Dental Admission Test (DAT), participation in a pipeline program, and undergraduate transcripts; academic records from the first term of dental school (class rank, course remediation, and withdrawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Our analyses showed that students’ past academic performance was associated with lower GPA trajectories and withdrawal or repeating years. This is consistent with prior studies that showed a positive association between student academic performance in dental school and their past performance, such as pre‐dental (undergraduate) GPA as well as Dental Admission Test scores 19,20 . Furthermore, the trajectories of academic performance in dental students that were observed in this study did not intersect, and the order (i.e., highest, middle, and lowest) remained stable during the study period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analyses showed that students’ past academic performance was associated with lower GPA trajectories and withdrawal or repeating years. This is consistent with prior studies that showed a positive association between student academic performance in dental school and their past performance, such as pre‐dental (undergraduate) GPA as well as Dental Admission Test scores 19,20 . Furthermore, the trajectories of academic performance in dental students that were observed in this study did not intersect, and the order (i.e., highest, middle, and lowest) remained stable during the study period.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with prior studies that showed a positive association between student academic performance in dental school and their past performance, such as pre-dental (undergraduate) GPA as well as Dental Admission Test scores. 19,20 Furthermore, the trajectories of academic performance in dental students that were observed in this study did not intersect, and the order (i.e., highest, middle, and lowest) remained stable during the study period. This result is in line with prior studies that demonstrated a positive association between first-year GPA in dental school and later academic performance in dental school.…”
Section: Discussionmentioning
confidence: 60%
“…Typically, admissions to the dental hygiene program require at least one year of college and the completion of prerequisite courses, including anatomy, biology, chemistry, microbiology, and math. Interestingly, in a recent analysis of predictive factors for student success in dental school, Sabato et al showed that the elements of undergraduate education could help identify students who are at risk for poor performance and require timely intervention [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of dental admission scores to a school's competency exams for fourth‐year students found the DAT—Perceptual Ability Test (PAT) to be a statistically significant predictor of performance 11 . Another analysis of student performance in the first‐year of dental school showed the DAT‐PAT to be positively related to academic performance 12 . The previously referenced Canadian study also found reading comprehension (RC), chemistry, and PAT portions of the DAT to be significantly related to annual GPA for all 4 years of dental school 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A study of a master's program focused on preparing students for professional school found DATs and completion of a preprofessional physiology course to be positively related to success in dental school classes 14 . In contrast, students who took organic chemistry in a summer term were more likely to face academic difficulty in dental school 12 …”
Section: Introductionmentioning
confidence: 99%